Teknik Budidaya Lobster (Cherax quadricarinatus) Air Tawar di Balai Budidaya Air Tawar (BBAT) Tatelu - Lengka, Kedis; Kolopita, Magdalena (e-Journal BUDIDAYA PERAIRAN, 2013)
The aimed of this field practice was to study the hatchery technique of freshwater lobster at Board of Freshwater Aquaculture, Tatelu (BBAT). During this practice, all the hatchery activities were conducted according to BBAT standar procedures. The number of broodstocks used in this practice was 225 females and 53 males. These broodstocks were propagated in mating pond for two weeks. Broodstocks having eggs were moved into hatching tank individually. Afterward, broodstock was removed into another tank while larvae were kept in hatching tank for 10 days. Larvae were cultivated in concrete tank for one month. Data collected included surviral rate, weight and length of lobster, and water quality. Survival rate of larvae was 50%. Water quality in broodstock tank was temperature 28,4 0C, pH 7,5; DO 5,6 mg/l, in hatching pond was temperature 27,23 0C, pH 7,5; DO 5,2 mg/l. In general, lobster hatchery consisted of tank preparation, boroodstock culture, broodstock seletion, hatching, larvae rearing, feeding, water quality contol, pest and disease prevention, harvest. Key Words: Hatchery, lobster, broodstocks.